Long term outcome after treatment of de novo coronary artery lesions using three different drug coated balloons. (15th February 2021) - Venetsanos, D.; Omerovic, E.; Sarno, G.; Pagonis, C.; Witt, N.; Calais, F.; Böhm, F.; Jurga, J.; Völz, S.; Koul, S.; Olivercrona, G.; James, S.; et al.
Abstract: Objective: To evaluate the long-term efficacy of three currently available drug coated balloons (DCB) for the treatment of de-novo coronary lesions. Methods: This was a retrospective analysis of prospectively collected data from the Swedish Coronary Angiography and Angioplasty Registry. Between 2009 and 2017, three currently available DCB brands used in the treatment of de novo lesions were included. Outcomes were clinically driven restenosis and target lesion thrombosis (TLT) (per device) and major adverse cardiac events (MACE) including death, myocardial infarction or target vessel revascularization (per patient) at 4 years. Multivariable Cox regression models were used to adjust for differences. Results: We included 6715 lesions treated with DCBs, 4483 SeQuent® Please (S-DCB), 1071 IN.PACT Falcon (I-DCB) and 1161 Pantera® Lux (P-DCB), in 5670 patients. The mean DCB diameter was 2.4 mm. Bailout stenting occurred in 6.7% of lesions. Angiographic success was 98.5%. The overall cumulative rate of restenosis was 5.5% (299 events). The risk for reported restenosis did not significantly differ between I-DCB vs S-DCB, adjusted hazard ratio (aHR) 0.96; 95% confidence interval (CI) 0.69–1.34, P-DCB vs S-DCB aHR 0.88; 95% CI 0.63–1.23 and I-DCB vs P-DCB aHR 1.10; 95% CI 0.72–1.68. The cumulative risk for TLT was 0.8% in all three DCBs. The risk for MACE or individual components of MACE did not differ between the three patient-groups. Conclusion: In de novo coronary lesions, we found comparable long-term efficacy with three currently available DCB brands. DCB angioplasty was feasible with low risk for long-term restenosis and TLT. Highlights: We found similar efficacy with three commercially available DCBs. The restenosis rate was low, even during long-term follow-up. DCB angioplasty appears feasible also in de novo lesion.